MOTIVASI BERPRESTASI MAHASISWA YANG MENGIKUTI AJANG PEMILIHAN MAHASISWA BERPRESTASI (PILMAPRES) UNIVERSITAS RIAU - Ricky Dwi Bintanio; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
A message has a different meaning between one individual and another. Then the message relates to the interpretation problem that received it. The present meaning is a social construction. This research aims to determine the motivation of students in the achievement of Riau University in 2019 female gender. The research informant is a student who participated in the selection of outstanding student (PILMAPRES) Riau university of 2019 especially female student located in the University of Riau. In this research the authors used purposive sampling techniques where this technique includes the people selected on the basis of certain criteria made based on research objectives. Then the data is analyzed using qualitative method. In this research, the author finds the character of the background difference between the informant which does not affect the motivation of the informant in participating in the outstanding student selection and in following the process of learning teaching in the classroom. For her, the pattern of life on campus and environment is very influential in participating pilmapres. In addition, the authors find that the meaning of education is very important considering that education includes a fundamental need for every individual, including (1) Education as a container of self-development, and (2) education as a supporting career and goals. The factors that encourage the informant to participate in outstanding student selection consist of various motives, including because the informant considers the outstanding student selection as an event model role, a self-proving event and an event to add insight to every finalically.  Keywords : Outstanding Student, Motivation.